The Effects of Flipped Classroom in English Language Communicative Skills - Yakob, Shafiee; Jawawi, Rosmawijah; Shahrill, Masitah; Jaidin, Jainatul Halida (International Journal of Essential Competencies in Education, 2023)
This study investigates the effectiveness of Flipped Classroom in teaching speaking skills for an English communicative class as well as the students’ perceptions of this approach towards their learning experience. In the flipped classroom, students watched the videos and read the provided documents outside the classroom. In class, which was done virtually, group discussions, debates, and role-plays were conducted based on the content that they had watched before the class. Both the pre-test and post-test were the instruments used to measure effectiveness, and all eight students were interviewed to identify their perceptions of Flipped Classroom. This research found that this instructional method was effective in teaching speaking skills, as there were improvements in the post-test in comparison with the pre-test, where only three students managed to score above 50% while the rest failed. This study also revealed that the flipped classroom was beneficial to students as it helped them improve their speaking skills. Despite the problems they faced in class, their speaking skills improved tremendously.